Optical analysis of polymer powder materials for Selective Laser Sintering - Laumer, Tobias; Stichel, T.; Nagulin, K.; Schmidt, Michael (Polymer Testing, 2016)
This study increases the basic understanding of optical material properties of polymer powders used in selective laser sintering (SLS). Therefore, different polymer powder materials were analyzed regarding their optical material properties with an integration spheres measurement setup. By the measurements a direct connection between the absorption behavior of the solid material and the overall optical material characteristics of the same material in powdery form could be shown. The results were used to develop an advanced explanation model for the optical material properties of powders. At present, existing explanation models only consider the occurring of multiple reflections in the gaps between the particles to explain the overall optical material properties of powder materials. Thus, by also considering the absorption behavior of the single particles, the basic understanding of the beam-matter interaction and their effect on the optical material properties of powder materials can be expanded.
Created from Fastlane, Scopus look-up
Keywords: Additive manufacturing; Integration spheres; Material qualification; New materials; Optical material characteristics; Selective Laser Sintering